Theoretical model and experimental study of the influence of bearing inner clearance on bearing vibration. (July 2022) - Wang, Kai; Yang, Hongjuan; Wu, Han; Jiang, Shengfei
Highlights: The 2-degree-freedom rolling bearing was established. The number of balance points depends on the clearance of the rolling bearing. It generates chaotic vibrations. It provides satisfactory results and verifies the feasibility of the method. Abstract: During the installation and operation of transmission equipment, bearing clearance problems occur, which are also one of the main reasons for bearing failure. Therefore, research on bearing clearance has theoretical significance and engineering value. To determine the influence of bearing clearance on bearing vibration, the theoretical model of a 2-degree-freedom rolling bearing was established based on the dynamic characteristics of the bearing vibration. Based on Hertz elastic contact theory analysis of the dynamic characteristics of the rolling bearing, it was observed that for the tested bearings, the number of balance points of the inner ring of the bearing depends on the clearance of the bearing. When bearing inner clearance (e) e < 4.5 μ m is present in the bearing, a stable equilibrium point exists, and periodic vibration occurs in the inner ring of the bearing near the centre of the balance point. When a gap of ( e ⩾ 4.5 μ m ) is present, and the gap and rotational speed of the bearing increase continuously, the system generates chaotic vibrations, and the area in which the chaotic vibration occurs also increases. The experimental results of the ϕ 127 m m rolling bearing indicated that under the same damping parameters, bearing size and rotational speed, the results of the singular attractors obtained from the experimental data are similar to those obtained by solving the equation of motion. This qualitative result not only confirms the existence of chaotic bearing behaviour, but also verifies the reliability of the theoretical model.